STRATEGI GURU PAI DALAM MENGHADAPI PESERTA DIDIK MALAS BELAJAR DI SDN 154 MANGKULANDE - Pratama, Fahri; Mustamin; Wahab, Abdul; Ahmad; Burhanuddin, Muh Azhar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of the role of Islamic Religious Education (PAI) teachers in creating engaging learning, particularly in a pluralistic educational environment. Teachers are required to be able to use appropriate learning approaches so that students have enthusiasm and motivation in participating in the learning process. Therefore, this study aims to determine: (1) the strategies of Islamic Religious Education (PAI) teachers in dealing with students who are lazy to learn, and (2) the inhibiting and supporting factors in the implementation of these strategies. This study uses a descriptive research type with a qualitative approach. The research data sources are Islamic Religious Education (PAI) teachers and class V.A students of SD Negeri 154 Mangkulande, East Luwu Regency. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions or verification. The results of the study indicate that Islamic Religious Education (PAI) teachers' strategies in dealing with students who are lazy to learn are carried out through individual, collaborative, and inclusive approaches. Teachers strive to understand student characteristics, create a pleasant learning atmosphere, and use varied learning methods that are relevant to everyday life. Supporting factors include the creation of a positive learning environment, the use of interesting methods, and the existence of interaction and collaboration in learning. Meanwhile, inhibiting factors include low student interest and motivation, lack of understanding of the material, and limited interaction between teachers and students. Therefore, ongoing efforts by teachers are needed to create effective and meaningful learning.